Internal Audit and Management of Operational and Financial Risks: Array - Moscu, Marius Daniel (Journal of Danubian Studies and Research, 2020)
Companies that have the obligation to audit the financial statements, as well as those who wish to do so on their own initiative, have the obligation to set up an internal audit service. Internal auditors may have a considerable influence on the operational efficiency and effectiveness of the entity, as well as on treasury and profit flows. Internal auditors carry out an important part of financial audit work, similar to those performed by independent external auditors. Many of the concepts and methods of financial audit also apply to internal audit audits. Internal auditors devote their entire working time to a single economic entity. Consequently, their knowledge of the entity's operations and internal control mechanisms are far more profound than those obtained by external financial auditors. Internal audit includes the examination and assessment of the adequacy and effectiveness of the entity's internal control system, as well as the assessment of the quality of the tasks assigned to each employee.